Effect of different wavelengths of light on growth, pigment content and protein amount of chlorella vulgaris - Kendirlioglu, Gokce; Kadri Cetin, A. (Parlar Scientific Publications, 2017)
Algae constitute the main source of materials that can be used as raw materials for many highvalue bioproducts, the most prominent ones of which are vitamins, lipids, chlorophyll and carotenoids. The key to economic production of biomass and bioproducts from microalgae is to optimize their growth conditions. Microalgae require optimal lighting conditions for efficient photosynthesis. Photoperiod, light intensity and wavelength of light are some of the important factors affecting the rate of photosynthesis. Light conditions directly affect the growth, pigment content and protein amount in microalgae. The aim of this study is to show the effects of light wavelength on growth, pigment content and protein amount in Chlorella vulgaris. Different wavelengths of light (blue, green, red and white light) were used to test their effects on growth, pigment content and protein amount in Chlorella vulgaris. The results show that the highest growth and amount of protein in Chlorella vulgaris were in cultures illuminated with red light. The amounts of chlorophyll and astaxanthin reached their highest values under different lights. The highest amounts of chlorophyll a and chlorophyll b were observed in cultures illuminated with green light while the highest amount of astaxanthin was observed in cultures illuminated with blue light. © by PSP.
Keywords: Astaxanthin; Chlorella vulgaris; Chlorophylls; Protein; Wavelength